Rational design of multifunctional superoleophobic/superhydrophilic, photocatalytic, and fire-retardant polyethylene terephthalate fabrics through layer-by-layer technique. (1st November 2020) - Peng, Shan; Wang, Yingchun; Lan, Yanrong; Shi, Xiaomeng; Zhang, Han; Qu, Hongqiang; Xu, Jianzhong
Abstract: In this study, a layer-by-layer (LBL) method was adopted to firstly fabricate superoleophobic, superhydrophilic, photocatalytic, and flame-retardant polyethylene terephthalate (PET) fabric. The fabric obtained self-extinguished fire retardance through alternative adsorption of charged branched poly(ethylenimine) (BPEI), phytic acid (PA), and ammonium polyphosphate (APP), and this was achieved by repeated assembly of only two bilayers (BL). The coating solution consisting of fluorosurfactant (capstone FS-50) with negative charge and TiO2 particle was further assembled onto the fire-retardant fabric surface, thus endowing it with superoleophobicity (both in air and water environments) and instant superhydrophilicity. Owing to the wettability differences to water and oil, the coated surface could be used to effectively and directly separate various oil-water mixtures without prewetting. It even acquired robust stability that could separate mixtures of oil with strong corrosive liquids, hot water or ice water. Because of its high superhydrophilicity, the developed surface could also separate various oil-in-water emulsions with high efficiency. Such a surface successfully solved the easy oil-fouling problem of separation membranes by blocking the oil and only allowing water to infiltrate, which led to high recyclability of the surface. Moreover, the introduction of TiO2 particles endowed the surface with superior photocatalytic ability both in air and under water environments. Graphical abstract: Image 1 Highlights: Superoleophobic and flame-retardant PET fabrics were fabricated via layer-by-layer method. Self-extinguished flame retardance was obtained through assembling only two bilayers. The PET fabrics efficiently separated oil-water mixtures/oil-in-water emulsions. The PET fabrics presented photocatalytic capability both in air and under water. The PET fabrics owned high recyclability.